The Effect of Job Embeddedness Dimensions On Intention to Quit among Employees In the Mobile Service Company in Egypt - Aboseif, Rasha (The Arab Journal of Administration, 2023)
This study aims to identify the effect of the dimensions of Job Embeddedness (organizational links, organizational Fits, organizational scarify, community Links, community Fits, and community scarify) on the intention to Quit. The study problem was identified in the form of a major question about the extent of the impact of the dimensions of Job Embeddedness on the intention to Quit, and developed a main hypothesis for the study, six sub-hypotheses emerged from it. The study used the questionnaire list to collect the data. The study was conducted on a sample (375) of workers in three companies (Orange, Vodafone, and Etisalat) providing mobile phone services in the Arab Republic of Egypt, and the sample was selected from a population of (11785) individuals. The statical analysis were using the Statistical Package for Social Sciences (SPSS / PC) Version. 23) and (AMOS 21) program. The study found a set of results. The results reached that there was a significant negative effect between organizational (link, fit, and scarify) on intention to quit, and no significant effect between community (link, fit, and scarify) on intention to quit. In the light of these results, the study recommends granting workers more freedom and independence in work and enhancing the culture of participation, activating work teams, supporting formal and informal communication channels, pay attention to work conditions, compensation policies, and pay attention to developing the career path of workers.